The Influence of Shopping Lifestyle and Fashion Involvement on Impulse Buying - zahara meuita (Institute of Computer Science (IOCS), 2021)
Business in Indonesia growth rapidly. One of the factors that influence the growth of the retail business is the very rapid growth in the number of consumers, especially middle-class consumers in Indonesia. Currently, shopping is not only to meet needs, the influence of trends in the community creates an impulse to view that shopping is a necessity and demands to buy the product or item. The era of globalization has brought people into consumptive behavior, where shopping has become a lifestyle. Therefore, the researcher intends to determine the effect of shopping lifestyle and fashion involvement on impulse purchases. The method in this study is a literature study based on previous research with criteria that are in accordance with the research variables. Based on several studies above, shopping lifestyle and fashion knowledge are important aspects in the occurrence of impulse buying. The influencing indicators are Trend, positive emotion, product brand, consumer characteristics, fashion knowledge, buying behavior, self-confidence and advertising,